Remuneration of veterinary specialists of the State Veterinary Service in the Russian Federation Subjects - I. M. Klinovitskaya; M. A. Shibayev; A. K. Karaulov; A. M. Selyanin (Ветеринария сегодня, 2023)
Remuneration is one of the main factors that can motivate an employee to work productively, as well as influence the prestige of a profession. The paper presents the results of analysis of remuneration of the veterinary specialists of the State Veterinary Service for the country as a whole, for the federal districts and 85 regions of the country, as well as at various organizational levels within the Veterinary Service for 2021. The assessment of the veterinary specialist salary level as compared with that throughout the economy of the Russian Federation Subjects is presented. The veterinary specialist average monthly salary for the State Veterinary Service as a whole varies within a wide range: from 16.3 to 114.9 thousand rubles. The minimum and maximum salaries at different organizational levels within the State Veterinary Service differ 5–8-fold. The veterinary specialist salary level is lower than that for the economy of the relevant Russian Federation Subject: for the State Veterinary Service as a whole – in 69 regions of the country, for treatment and preventive care institutions – in 71 Subjects, in laboratory diagnosis institutions – in 72 Subjects. Of all the federal districts, the North Caucasian Federal District has the lowest veterinary specialist salary level both in absolute terms (about 21 thousand rubles) and as compared with the average for the economy of the Subjects of this federal district (64%). The paper also examines veterinary specialist modal and median salary values, which allow for the assessment of remuneration of this category of the State Veterinary Service staff from different viewpoints.